Pengaruh Pengeluaran Pemerintah dan Investasi Terhadap PDRB HK di Provinsi Sumatera Utara: Penelitian - Monika Caramoy Sitorus; Selpiana Selpiana; Rouli Pranatalia Simnjuntak; William Barker Hutabarat; Muhammad Alhasymi Matondang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of government expenditure and investment on the Constant Price Gross Regional Domestic Product (PDRB) in North Sumatra Province. A quantitative approach with multiple linear regression design was used, with government expenditure and investment as independent variables and PDRB as the dependent variable. Secondary data from 2010 to 2024 were collected from the Central Statistics Agency of North Sumatra Province. The analysis was conducted using Ordinary Least Squares (OLS) estimation, including classical assumption tests, partial (t) and simultaneous (F) significance tests, and determination coefficient (R²). The results indicate that government expenditure has a positive and significant effect on PDRB, investment also exerts a positive and significant effect, and together both variables have a significant simultaneous impact on regional economic growth. These findings emphasize the importance of coordinating fiscal policies and investment strategies to promote sustainable economic growth. The study provides empirical evidence that can serve as a reference for regional governments in designing more efficient and effective development policies and budget allocation to enhance production capacity and public welfare.